Expression and function of Kv1.1 potassium channels in human atria from patients with atrial fibrillation - Glasscock, Edward; Voigt, Niels; Zhou, Xiao-Bo; Thomas, Dierk; Schmidt, Constanze; Dobrev, Dobromir (Basic research in cardiology, 2015)
Voltage-gated Kv1.1 channels encoded by the Kcna1 gene are traditionally regarded as being neural-specific with no known expression or intrinsic functional role in the heart. However, recent studies in mice reveal low-level Kv1.1 expression in heart and cardiac abnormalities associated with Kv1.1-deficiency suggesting that the channel may have a previously unrecognized cardiac role. Therefore, this study tests the hypothesis that Kv1.1 channels are associated with arrhythmogenesis and contribute to intrinsic cardiac function. In intra-atrial burst pacing experiments, Kcna1-null mice exhibited increased susceptibility to atrial fibrillation (AF). The atria of Kcna1-null mice showed minimal Kv1 family ion channel remodeling and fibrosis as measured by qRT-PCR and Masson’s trichrome histology, respectively. Using RT-PCR, immunocytochemistry, and immunoblotting, KCNA1 mRNA and protein were detected in isolated mouse cardiomyocytes and human atria for the first time. Patients with chronic AF (cAF) showed no changes in KCNA1 mRNA levels relative to controls; however, they exhibited increases in atrial Kv1.1 protein levels, not seen in paroxysmal AF patients. Patch-clamp recordings of isolated human atrial myocytes revealed significant dendrotoxin-K (DTX-K)-sensitive outward current components that were significantly increased in cAF patients, reflecting a contribution by Kv1.1 channels. The concomitant increases in Kv1.1 protein and DTX-K-sensitive currents in atria of cAF patients suggest that the channel contributes to the pathological mechanisms of persistent AF. These findings provide evidence of an intrinsic cardiac role of Kv1.1 channels and indicate that they may contribute to atrial repolarization and AF susceptibility.